Prevalence of and risk factors for gout in HIV-positive adults: A case–control study. (March 2019) - Nicholson, Prini; Saunsbury, Emma; D'Angelo, Stefania; Churchill, Duncan; Walker-Bone, Karen
Gout is the most common inflammatory arthritis worldwide. Its principal risk factor is hyperuricaemia. While gout has been described in HIV patients and numerous more outdated anti-retroviral therapies (ARTs) have been implicated, there have been few recent studies. Our case–control study investigated the prevalence of and risk factors for gout in an established HIV cohort. Cases were identified from database searches using key search terms, with two age- and gender-matched controls. These were compared for demographic factors, co-morbidities, HIV factors and ART exposure. Forty-five cases with gout were identified (point prevalence 2.2%). All were male and were more likely than controls to be of black African origin. Hypertension was associated with an almost five-fold increased gout risk (OR 4.8, 95% CI 1.8–12.4). No individual drug or ART class was associated with gout in this study but exposure to non-nucleoside reverse transcriptase inhibitors had a significantly protective effect against the risk of gout (OR 0.3, 95% CI 0.1–0.9). Our data suggest that gout is common in HIV patients and that the traditional risk factors, especially hypertension, play a key role. Gout and hyperuricaemia should be regarded as a biomarker of cardiovascular disease in HIV patients as they are in the general population.